Query Dissemination in Sensor Networks - Predicting Reachability and Energy Consumption - Benenson, Zinaida; Freiling, Felix; Bestehorn, Markus; Böhm, Klemens; Buchmann, Erik; Jawurek, Marek (Ad Hoc & Sensor Wireless Networks Vol. 9, 2010)
Specifying information needs declaratively has turned out to be useful in the context of databases systems, and reseachers have applied this approach to sensor networks. The first step to retrieve data from a sensor network in this way is the dissemination of the query. Energy-efficient query dissemination plays an important role for the lifetime of sensor networks. The topic of this paper is the optimization of probabilistic query dissemination: Based on easy-to-acquire topology information, the optimizer can predict the number of nodes reached and the energy consumption. Furthermore, we propose a topology-discovery protocol that collects the structural information required by the optimizer. Our analysis shows that the energy savings exceed the energy spent to obtain the required information after a small number of queries disseminated in realistic settings. Our evaluation explores the tradeoff between reachability and energy consumption using both simulations and a deployment of Sun SPOT sensor nodes. © 2009 Old City Publishing, Inc.
UnivIS-Import:2015-04-16:Pub.2010.tech.IMMD.lehrst.queryd
Keywords: Broadcast optimization; Energy efficiency; Probabilistic broadcasting; Query dissemination; Wireless sensor networks

Query Dissemination with Predictable Reachability and Energy Usage in Sensor Networks - Benenson, Zinaida; Bestehorn, Markus; Buchmann, Erik; Freiling, Felix; Jawurek, Marek (Ad-hoc, Mobile and Wireless Networks, 7th International Conference (ADHOC-NOW), 2008)
Energy-efficient query dissemination plays an important role for the lifetime of sensor networks. In this work, we consider probabilistic flooding for query dissemination and develop an analytical framework which enables the base station to predict the energy consumed and the nodes reached according to the rebroadcast probability. Furthermore, we devise a topology discovery protocol that collects the structural information required for the framework. Our analysis shows that the energy savings exceed the energy spent to obtain the required information after a small number of query disseminations in realistic settings. We verified our results both with simulations and experiments using the SUN Spot nodes. © 2008 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-04-16:Pub.2008.tech.IMMD.lehrst.queryd